Aerial RIS-aided physical layer security design for satellite communication among similar channels - Chengjun Jiang; Chensi Zhang; Leilei Mu; Zhe Zhang; Jianhua Ge (Journal of Information and Intelligence)
Satellite communications and reconfigurable intelligent surface (RIS) are considered as two promising technologies that can significantly improve the coverage and energy efficiency of future wireless communication networks. The satellite communications security is often threatened due to its broadcasting nature. To enhance the physical layer security (PLS) of satellite communications with channel similarity, an aerial RIS-aided dual full-duplex (DFD-ARIS) cooperative jamming method is presented in this paper. Specifically, unlike the existing works that relied on channel difference, DFD-ARIS utilizes the channel similarity against the eavesdroppers with the help of ARIS. In addition, the power allocation is further studied in conjunction with the phase design of RIS to minimize the total power under the constraints of data rate, satellite power limitation and secrecy rate. Then, the closed-form solutions are achieved. Simulation results show that the performance of the proposed scheme is superior to the traditional method.